Review of the Sanctioning Power in Public Procurement: About the Plenary Court Agreement 1/2015-TCE issued by the State Procurement Court - Rubio Salcedo, César Rommel (2015)
On the basis of the revision of the power to impose on government procurement matter, the author analyses the content and scope of Plenary Court agreement 1/2015-TCE; to the light of the juridical and factual that will occur with the emission and issue of this binding precedent.In addition, the author works a prediction of the eventual contradictions on the application of the Plenary Court agreement that may occur in the juridical administrative system and the harmful consequences of the effectiveness of it.